Tungsten carbide is more oxidation resistant than tungsten when processed to full density. (15th April 2016) - Humphry-Baker, Samuel A.; Lee, William E.
Abstract: Previous studies report that WC oxidises in air more readily than W. However, systematic thermogravimetric studies reveal considerably slower oxidation kinetics in WC samples, which outperform previous measurements by 1–2 orders of magnitude. By combining X-ray diffraction and electron microscopy, the enhanced stability in WC is explained by a dense interlayer of sub-stoichiometric WO3, approximately 10 μm in thickness, which forms adjacent to the substrate/oxide interface. The faster oxidation kinetics from previous studies are explained by the comparatively low densities of samples used. Graphical abstract: